Ultrasmall PEI-Decorated Bi2Se3 Nanodots as a Multifunctional Theranostic Nanoplatform for in vivo CT Imaging-Guided Cancer Photothermal Therapy - Zhang, Peng; Wang, Lei; Chen, Xiuying; Li, Xiang; Yuan, Qinghai (Frontiers in Pharmacology, 2021)
Bi-based nanomaterials, such as Bi2Se3, play an significant role in the field of biomedicine, such as photothermal therapy (PTT) and computed tomography (CT) imaging. In this study, polyethylenimine (PEI)-modified ultrasmall Bi2Se3 nanodots were prepared using an ultrafast synthesis method at room temperature (25℃). These nanodots exhibit superior CT imaging performance, and can be used as effective photothermal reagents owing to their broad ultraviolet–visible–near infrared absorption. Moreover, under 808 nm irradiation, PEI-Bi2Se3 nanodots exhibit excellent photothermal conversion efficiency of up to 41.3%. Moreover, good biocompatibility and significant tumor ablation capabilities have been confirmed through in vitro and in vivo studies. All the positive results have revealed that the PEI-Bi2Se3 nanodots are safe and a good nanotheranostic platform for CT imaging-guided PTT of cancerous tumor.